Researching the Impact of Partial Labour Migration on a Child: Failure of Attachment Theory - Gedas Malinauskas (Social Work and Society)
The aim of the article is to introduce a research report revealing the peculiarities of children experience when their parents are in the process of partial labour migration. Partial labour migration is a specific form of migration when one or both parents leave to work abroad (for more than 3 months) and the rest of the family stays in Lithuania. In case of departure of both parents, children are looked after by grandparents or other family members (for example, aunt). The article is based on the data of the quantitative survey Trends and Peculiarities of Labour Migration in Kaunas undertaken in all kindergartens of Kaunas city (N=88). Parents who had the experience of working abroad were surveyed using questionnaire. A special focus in the article is on the review of the attachment theory drawbacks. With reference to the attachment theory, a hypothesis was put forward that children under 6 should experience separation difficulties when parting with one of parents for a long time since they loose the object of attachment related to safety. According to the theory, this should especially be revealed in cases when children are fostered by grandparents. The research showed that a quarter of children experienced short-term difficulties, whereas 10% of children were negatively influenced by the departure. The hypothesis that children who stayed with their grandparents experienced more problems was rejected for there was no differences between parents' opinion and that of grandparents found. The question is posed in the article: what theories are needed to define in greater detail the experience of children "in the family brake processe" when parents work abroad for a long time.